Understanding Responsible Investment in Private Equity: Challenges & Opportunities in Uganda - Obol, Daniel (Graduate School of Business (GSB), 2024)
Like many other developing countries in Africa, the growth and development of Uganda's economy is hinged on the level of progressive investment in the factors of production that include; land, labour, capital and entrepreneurship. Such investments create avenues through which resources that provide a comparative advantage for the country can be exploited to benefit all citizens. These benefits include creating more employment opportunities, increased tax revenue and foreign exchange inflows. Over the years, there has been a considerable reliance by the Government and private individuals on debt capital as a source of financing for development infrastructure, business growth and development, respectively. However, with the recent trends in the global world economy, including; the world financial crisis between 2007 and 2010 and the coronavirus pandemic between 2020 and 2022, debt capital has increasingly become less reliable given the increased risk aversion of lenders. Despite this, the Ugandan economy is endowed with vast resources that provide opportunities in commercial agriculture, tourism (Source of the Nile, home of Mountain Gorillas), and agroprocessing, among others. Developing countries like Uganda can tap into this opportunity given the low levels of development and employment that are well aligned to the objectives of impact, philanthropic and other developmental-based investors. However, private equity capital in Uganda is yet to be well utilized compared to countries like South Africa, Kenya, and Nigeria. The strategic importance of private equity has been further compounded by the fact that private equity investors, especially development finance institutions, have been critical advocators for responsible and impact investing worldwide. This study leverages interviews with 13 industry experts from the private equity market in Uganda, using a qualitative research approach, to establish the motivations behind private investments, the extent to which responsible investment is included in the decision-making process and the challenges encountered when raising capital in Uganda. The thematic analysis established that private equity investors in Uganda place key consideration on responsible investment, and more of this capital can be raised in the country. However, some inherent limitations exist and include; the inadequacies in the existing laws, the lack of preparedness of local entrepreneurs, and the limited participation of local institutional investors. Based on the findings from the research, some institutional recommendations, for example, the amendment of the current prohibitive Tax Laws, could go a long way in attracting more private equity capital into the country.